The association of endogenous sex hormones, adiposity, and insulin resistance with incident diabetes in postmenopausal women - Kalyani, Rita Rastogi; Franco, Manuel; Dobs, Adrian S; Ouyang, Pamela; Vaidya, Dhananjay; Bertoni, Alain; Gapstur, Susan M; Golden, Sherita Hill (The journal of clinical endocrinology and metabolism, 2009)
In postmenopausal women, endogenous bioavailable testosterone (T) and estradiol (E2) have been positively associated, and SHBG has been negatively associated, with incident type 2 diabetes (T2DM). Previous studies have not explored possible factors explaining these relationships. Our objective was to examine the association of endogenous sex hormones with incident T2DM in postmenopausal women and possible explanatory factors. The Multi-Ethnic Study of Atherosclerosis (MESA) is a prospective study that included 1612 postmenopausal women aged 45-84 yr, followed between the years 2000-2006, who were not taking hormone replacement therapy, had no prevalent cardiovascular disease or diabetes, and had complete ascertainment of sex hormones. T2DM was defined based on fasting glucose and/or treatment for diabetes. There were 116 incident cases of diabetes during follow-up. Across higher quartiles of bioavailable T and E2 and lower quartiles of SHBG, we found significantly greater hazards of developing incident T2DM (all P for trend <or=0.001). After adjustment for body mass index and insulin resistance estimated by homeostasis model assessment of insulin resistance, bioavailable T was no longer associated with incident T2DM. The associations of E2 and SHBG with incident T2DM were partially explained by body mass index and insulin resistance but persisted in fully adjusted models (both P for trend <0.02). Dehydroepiandrosterone had no relationship with incident T2DM. Adiposity and insulin resistance explained most of the association of bioavailable T but only partially explained the associations of E2 and SHBG with incident T2DM among postmenopausal women.